Comparative enantioseparation of planar chiral ferrocenes on polysaccharide‐based chiral stationary phases. Issue 4 (24th January 2022) - Dessì, Alessandro; Sechi, Barbara; Dallocchio, Roberto; Chankvetadze, Bezhan; Pérez‐Baeza, Mireia; Cossu, Sergio; Mamane, Victor; Pale, Patrick; Peluso, Paola
Abstract: Planar chiral ferrocenes are well‐known compounds that have attracted interest for application in synthesis, catalysis, material science, and medicinal chemistry for several decades. In spite of the fact that asymmetric synthesis procedures for obtaining enantiomerically enriched ferrocenes are available, sometimes, the accessible enantiomeric excess of the chiral products is unsatisfactory. In such cases and for resolution of racemic planar chiral ferrocenes, enantioselective high‐performance liquid chromatography (HPLC) on polysaccharide‐based chiral stationary phases (CSPs) has been used in quite a few literature articles. However, although moderate/high enantioselectivities have been obtained for planar chiral ferrocenes bearing polar substituents, the enantioseparation of derivatives containing halogens, or exclusively alkyl groups, remains rather challenging. In this study, the enantioseparation of ten planar chiral 1, 2‐ and 1, 3‐disubstituted ferrocenes was explored by using five polysaccharide‐based CSPs under multimodal elution conditions. Baseline enantioseparations were achieved for nine analytes with separation factors (α) ranging from 1.20 to 2.92. The presence of π‐extended systems in the analyte structure was shown to impact affinity of the most retained enantiomer toward amylose‐based selectors, observing retention times higher than 80 min with methanol‐containing mobile phases (MPs). Electrostatic potential (V) analysis and molecular dynamics (MD) simulations were used in order to study interaction modes at the molecular level. Abstract : High‐performance liquid chromatography (HPLC) enantioseparations of ten 1, 2‐ and 1, 3‐disubstituted planar chiral ferrocenes on five polysaccharide‐based chiral stationary phases (CSPs) were comparatively explored under multimodal elution conditions. The presence of π‐extended systems in the analyte structure was shown to impact affinity of the most retained enantiomer toward amylose‐based selectors, observing retention times higher than 80 min (k2  = 22.6, α = 8.9) with methanol‐containing mobile phases (MPs).